Bandgap determination and charge separation in Ag@TiO2 core shell nanoparticle films - Tunc, Ilknur; Bruns, Michael; Gliemann, Hartmut; Grunze, Michael; Koelsch, Patrick (Surface and interface analysis, 2010)
The photocatalytic activity of TiO2 under sunlight irradiation depends on the bandgap energy. Due to the relatively low solar intensity in the UV region (<10%) and the fact that the bandgap of TiO2 is usually greater than 3 eV (below 400 nm), many attempts have been made to shift the bandgap towards lower energies. Here, we investigate the structure, chemical composition, bandgap shift and charge transfer processes of Ag@TiO2 core‐shell nanoparticle thin films by field emission scanning electron microscopy, atomic force microscopy, XPS, and UV‐Vis spectroscopy. As a solid support, Au‐coated Si wafers and Si surface covered with a native oxide were used and homogenously covered by Ag@TiO2 core‐shell nanoparticles with overall film thicknesses of 80–100 nm and size distributions between 8 and 15 nm. The shell thickness of the adsorbed Ag@TiO2 particles was estimated to be 1.5‐2.0 nm. The effect of the Ag core on the bandgap of TiO2 and photoinduced charge separation of Ag@TiO2 nanoparticle films was studied by UV‐Vis reflectance spectroscopy using the Kubelka‐Munk formalism. Films of Ag@TiO2 core‐shell nanoparticles revealed a substantially reduced bandgap of 2.75 eV (corresponding to 450 nm), and an electron charge transfer to the Ag core occurring upon UV irradiation on nonconductive surfaces. These features make Ag@TiO2 particulate films a promising candidate for photocatalytic surfaces under sunlight irradiation. Copyright © 2010 John Wiley & Sons, Ltd.